Operational experience of GNSS receivers with Chip Scale Atomic Clocks for baseline measurements - Karpik, Alexander P.; Kosarev, Nikolay S.; Antonovich, Konstantin M.; Ganagina, Irina G.; Timofeev, Vladimir Yu. (Geodesy and Cartography, 2018)
Currently, one of the topical issues of improving GLONASS system is modernization of its uniformity measurement equipment, including RF measurement equipment and electronic length measurement equipment. To this end, at the Spatial Reference Proving Ground of theSiberian State University of Geosystems and Technologies (SSUGT), the authors of this article carried out a successful experiment to measure a short GNSS baseline by receivers equipped with Chip Scale Atomic Clocks (CSACs) with instability of 10−11 showed that the mean deviation between the slant distance (D) measured using GNSS receivers connected to CSACs and their certified value varied in the range of 0.1–2.5 mm, with the average value of 0.9 mm. The mean deviation obtained using GNSS geodetic receivers not connected to CSAC and their certified value made up 9.4 mm.The obtained experimental results suggest that substitution of quartz frequency generators with temperature compensation used in geodetic GNSS receivers for Chip Scale Atomic Clocks in any metrological or verification kit increases accuracy and reliability of short baselines measurements results, which highly perspective in view of development of techniques for creating reference baselines with a reproduction error of unit length of about 1 mm per 1 km.The above-mentioned experiment opens up new horizons for the use of Chip Scale Atomic Clocks in such fields of science as metrological support of geodetic equipment, geodesy, etc.